2016
DOI: 10.4103/2231-0762.181168
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of smile line, gingival angle and tooth shape among the Saudi Arabian subpopulation and their association with gingival biotype

Abstract: Objectives:To determine the occurrence of smile line and maxillary tooth shape in the Saudi Arabian subpopulation, and to estimate the association between these parameters with gingival biotype.Materials and Methods:On the fulfillment of selection criteria, total 315 patients belong to Saudi Arabian ethnic group were randomly selected. Two frontal photographs of the patients were acquired. The tooth morphology, gingival angle, and smile line classification were determined with ImageJ image analyzing software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…According to Yoon et al 55.83% of the Korean population has the medium SL, 29.17% have the high SL, and 15% have the low SL (15). In the study they conducted, AlQahtani et al determined that the medium SL was observed in 57.5% of the Saudi Arabian population, the high SL was observed in 24.1%, and the low SL was observed in 18.4% (16). According to the results obtained from the present study, the most common SL in the young Turkish population is the medium SL (45.3%), and the least common SL is the high SL (18.4%).…”
Section: Discussionmentioning
confidence: 99%
“…According to Yoon et al 55.83% of the Korean population has the medium SL, 29.17% have the high SL, and 15% have the low SL (15). In the study they conducted, AlQahtani et al determined that the medium SL was observed in 57.5% of the Saudi Arabian population, the high SL was observed in 24.1%, and the low SL was observed in 18.4% (16). According to the results obtained from the present study, the most common SL in the young Turkish population is the medium SL (45.3%), and the least common SL is the high SL (18.4%).…”
Section: Discussionmentioning
confidence: 99%
“…AlQahtani et al evaluated the smile line, gingival angle, and tooth shape among a subpopulation of the Saudi Arabia and their connection with gingival biotype. 9 They concluded statistically significant relationship between thick gingival biotype, the square tooth, and high smile line. The high gingival angle was allied with thin gingival biotype.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, few criteria are used for smile analyses of young individuals [ 6 , 7 , 10 , 12 , 24 , 25 ]. The purpose of this study was to evaluate and analyse dentogingival macro-aesthetic elements of the smile of young adults within Al Qassim Province.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving different populations have provided evidence that aesthetic components for different sexes, races, and ages are not entirely the same [ 4 6 ]. However, the number of studies conducted to assess smile parameters within the Saudi population is minimal [ 6 , 7 ]. Additionally, results of these studies were variable and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation